PEMAKSAAN HUBUNGAN SEKSUAL SUAMI TERHADAP ISTRI (MARITAL RAPE) (STUDI KOMPARATIF HUKUM POSITIF DAN HUKUM ISLAM) - Pitrotussaadah fitroh; Sulfan Alamsyah (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2023)
This paper is a forced sexual relationship of husband against wife (marital rape) (comparative study of positive law and Islamic law). Conjugal sexual intercourse is a natural need that must be fulfilled by both parties but without coercion in it that causes one of them to be hurt. In practice, this is not the case, sometimes husbands ask to have sex at inappropriate times such as when the wife is not good physically, hormonally or psychologically, and generally husbands do not understand the condition of the wife and lead to coercion or even violence in sexual intercourse which results in one of them being harmed because with this condition the wife cannot enjoy it but hurt her. So how positive law and Islamic law address the problem. This paper aims to understand marital rape law in positive law and Islamic law. Based on the qualitative method of library research with a comparative descriptive approach, it can be concluded that domestic rape is an unnatural thing done by the husband to the wife because it can hurt the wife because it does not pay attention to the physical and psychological condition of the wife. Whereas in Islamic law if the coercion by the husband against the wife is still within reasonable limits, then it is not a problem. However, if coercion is accompanied, threats and violence while the physical and psychological conditions and conditions of the wife are not possible to serve her husband such as being sick, menstruating, tired, and other shari'i old age that is considered appropriate, then the husband can be categorized as marital rape and the perpetrator is subject to ta'zir whose punishment is determined by a judge.